A Comprehensive Model That Explains the Regulation of Phospholipase D2 Activity by Phosphorylation-Dephosphorylation - Henkels, Karen M. (American Society for Microbiology (ASM), 2010)
We report here that the enzymatic activity of phospholipase D2 (PLD2) is regulated by phosphorylation-dephosphorylation. Phosphatase treatment of PLD2-overexpressing cells showed a biphasic nature of changes in activity that indicated the existence of “activator” and “inhibitory” sites. We identified three kinases capable of phosphorylating PLD2 in vitro—epidermal growth factor receptor (EGFR), JAK3, and Src (with JAK3 reported for the first time in this study)—that phosphorylate an inhibitory, an activator, and an ambivalent (one that can yield either effect) site, respectively. Mass spectrometry analyses indicated the target of each of these kinases as Y(296) for EGFR, Y(415) for JAK3, and Y(511) for Src. The extent to which each site is activated or inhibited depends on the cell type considered. In COS-7, cells that show the highest level of PLD2 activity, the Y(415) is a prominent site, and JAK3 compensates the negative modulation by EGFR on Y(296). In MCF-7, cells that show the lowest level of PLD2 activity, the converse is the case, with Y(296) unable to compensate the positive modulation by Y(415). MTLn3, with medium to low levels of lipase activity, show an intermediate pattern of regulation but closer to MCF-7 than to COS-7 cells. The negative effect of EGFR on the two cancer cell lines MTLn3 and MCF-7 is further proven by RNA silencing experiments that yield COS-7 showing lower PLD2 activity, and MTLn3 and MCF-7 cells showing an elevated activity. MCF-7 is a cancer cell line derived from a low-aggressive/invasive form of breast cancer that has relatively low levels of PLD activity. We propose that PLD2 activity is low in the breast cancer cell line MCF-7 because it is kept downregulated by tyrosyl phosphorylation of Y(296) by EGFR kinase. Thus, phosphorylation of PLD2-Y(296) could be the signal for lowering the level of PLD2 activity in transformed cells with low invasive capabilities.